Strategic Transformation of Human Capital Development to Enhance Professionalism in the Luwu Timur Civil Service Police Unit - St Reski Amalia; Mahadir Muhammad AK; Hariati; Muchriadi Muchran (Yayasan Amerta Insan Unggul, 2026)
This study examines the strategic transformation of Human Capital Development (HCD) in enhancing professionalism within the Luwu Timur Civil Service Police Unit. The research addresses persistent structural, cultural, and managerial gaps that hinder competence, digital readiness, and service quality in local enforcement agencies. Employing a qualitative case study design, primary data were collected through semi-structured interviews, direct observations, and document analysis involving leaders, managers, frontline officers, and community members. The findings reveal that HCD practices remain reactive, fragmented, and unsupported by systematic competency mapping or structured training. Leadership demonstrates partial transformational characteristics, offering motivation but lacking consistent coaching and intellectual stimulation, which affects change readiness among personnel. Professionalism is evident in ethical conduct but remains inconsistent in technical competence and communication skills. This study proposes a four-pillar Strategic HCD Transformation Model comprising competency-based planning, digital learning, leadership enhancement, and professionalism standardization. The model provides theoretical contributions by integrating HCD and transformational leadership within public-sector organizational development and offers practical implications for local government agencies seeking to strengthen human capital, digital capability, and enforcement professionalism.